2011
DOI: 10.1111/j.1540-6229.2010.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wealth Effects of Property Acquisitions: Evidence from Japanese and Singaporean REITs

Abstract: This article examines the wealth effects of 228 property acquisition announcements made by REITs publicly traded in Singapore and Japan, which are the two largest REIT markets in Asia. Adopting an aggressive growth-byacquisition strategy, the newly listed REITs acquired a number of properties within a short time period. Despite their regular activities, we observe the acquisition announcements are associated with a significantly positive abnormal increase in shareholder wealth averaging 0.38% in a 5-day window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…These differences motivate us to conduct sub-sample analysis by country. For further institutional details on the REIT markets in Japan and Singapore, please refer to Ooi et al (2010). In contrast, there is no debt limit for US REITs.…”
mentioning
confidence: 96%
“…These differences motivate us to conduct sub-sample analysis by country. For further institutional details on the REIT markets in Japan and Singapore, please refer to Ooi et al (2010). In contrast, there is no debt limit for US REITs.…”
mentioning
confidence: 96%
“…The market, however, expects the managers to acquire reasonable assets to benefit to the unit holders, not just anticipate increasing asset under management and consequently management fees as in [39]. After announcements of new property acquisition of Singapore and Japan REITs, significant abnormal increase of unit value has been averagely found 0.38% in a five trading days around the event date as in [42]. However, [24] found that there is no benefits from size for EU REITs, especially after the subprime crisis.…”
Section: Asset Growth and Fund Size Increasementioning
confidence: 95%
“…In the context of REITs, Allen and Sirmans (1987) and Campbell et al (2003) document that REITs enjoy excess abnormal returns when acquiring other REITs or real estate portfolios. Ooi et al (2011) suggest that newly listed REITs can increase stockholder wealth by acquiring a number of properties.…”
Section: Literature Reviewmentioning
confidence: 99%